GENOGRAM UNTUK MENGEMBANGKAN KEMAMPUAN PERENCANAAN KARIR SISWA SMP - Rima Irmayanti (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
At junior high school students, career planning decisions are influenced by the environment, especially families. information about family influences in making career decisions can be obtained through the genogram. This research, in general, aims to derive empirical facts about the effectiveness of the genogram to develop the career planning skills of junior high school students, in particular, the aim of this study is to obtain a profile of students' career planning abilities; formulation of the genogram technique based on the student's career planning ability profile; and an overview of the effectiveness of the genogram to develop students' career planning skills. The research design used is one group pretest-postest. To obtain data of research result used instrument of career planning ability. The population of this study are students of class VIII SMP Negeri 43 Bandung, with sample research VIII-1. Data analysis is done quantitatively. The result of the research shows that students' career planning ability after the statistical technique of genogram has changed to better, that is, there is a significant difference between the improvement of career planning ability of upper, middle, and lower students in pre test and post test.